2014
DOI: 10.1186/1878-5085-5-4
|View full text |Cite|
|
Sign up to set email alerts
|

Traditional Chinese medicine and new concepts of predictive, preventive and personalized medicine in diagnosis and treatment of suboptimal health

Abstract: BackgroundThe premise of disease-related phenotypes is the definition of the counterpart normality in medical sciences. Contrary to clinical practices that can be carefully planned according to clinical needs, heterogeneity and uncontrollability is the essence of humans in carrying out health studies. Full characterization of consistent phenotypes that define the general population is the basis to individual difference normalization in personalized medicine. Self-claimed normal status may not represent health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 26 publications
3
100
0
Order By: Relevance
“…But this definition is still a controversy for in the research of intension about health, there are problems as obscurities in definition [36]. [27,28,37]. Results in this study indicate a high prevalence of SHS among the sample population (46%), which is similar to previous reports [24,38].…”
Section: Breakfast Eating Habits and Shssupporting
confidence: 82%
See 1 more Smart Citation
“…But this definition is still a controversy for in the research of intension about health, there are problems as obscurities in definition [36]. [27,28,37]. Results in this study indicate a high prevalence of SHS among the sample population (46%), which is similar to previous reports [24,38].…”
Section: Breakfast Eating Habits and Shssupporting
confidence: 82%
“…A previous investigation by the current authors found that suboptimal health status was applicable to 65.1% of the surveyed population in Southern China [24], with SHS now a major global public health challenge [20,25,26]. Current prevention and intervention strategies recommend disease prevention and effective treatment of early-stage illness [27,28]. However, both the etiology and mechanisms associated with SHS require further elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, Shao et al [27] did a first attempt to map the medical care ecology of Beijing urban population, which would be useful for highlighting health care system reform, the formulation of better health care policy and improving medical education to meet the expanding demands of the people. Beyond that, Wang et al [28] had developed a questionnaire-suboptimal health status questionnaire-25 (SHSQ-25), which could be used as an effective instrument for predictive, preventive and personalized medicine, and would enable clinicians and public health workers to predict an individual's predisposition, such as prehypertension in order to provide targeted preventive measures before the actual onset of the disease. However, the awareness and control rates in northeast Our present findings also showed that subjects who were overweight/obesity or those with dyslipidemia or diabetes tended to be more aware of their hypertension than those without these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the concept of suboptimal health status (SHS) was advocated from the perspective of predictive, preventive, and personalized medicine [23,24]. SHS is characterized by ambiguous health complaints and recognized as a subclinical, reversible stage of chronic disease.…”
Section: Discussionmentioning
confidence: 99%